The Effect of Systematic Risk, Operating Cash Flow and Growth Opportunities on Future Earnings Response Coefficients (FERC), Working Capital as A Moderation Variable - Wiguna, Sunanta; Murwaningsari, Etty (International Journal of Social and Management Studies, 2022)
Purpose this research to analyze effect of systematic risk (SR), operating cash flow (OCF) and also growth opportunities (Growth) on the future earnings response coefficient (FERC) moderated by working capital requirements (WCR). This quantitative study uses 245 data on manufacturing companies listed Indonesia Stock Exchange period 2015-2019. Analysis technique utilized multiple linear regression. The Results indicate that SR has significant negative effect on FERC while growth has no effect on FERC. WCR as moderation of the effect of SR and Growth on FERC weakens the previous effect. OCF was eliminated in the study. Timeliness as control variable has significant effect on FERC while Size, Profitability and Leverage have no effect on FERC.